Ozone as an Adjunct Therapy in Canine Parvo Virus Infection in Dogs - Nagarkar, Pranay; Ambore, Balaji; Jadhav, Ravindra; Ranganekar, Mahesh; Mote, Chandrakant; Jadhav, Sameer (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Canine Parvovirus infection is highly infectious disease of younger dogs with high mortality rates. A total of 1026 dogs presented at Veterinary Clinical Complex of the College in Shirwal were screened, out of which 33 dogs (3.2%) were confirmed positive for CPV using rapid antigen test, which were further confirmed by PCR. Twenty affected dogs were selected and divided into two treatment groups: Group 2 (standard ceftriaxone + supportive therapy) and Group 3 (ozonated RL as an adjunct therapy along with standard treatment), each comprising 10 animals, while 10 healthy dogs served as control Group-I. Haematological findings revealed a significant (p
Keywords: Adjunct therapy; Canine parvo virus; Ozone